The - editors in chief; Cathy N. Davidson; Linda Wagner-Martin; editors Elizabeth Ammons ... (Oxford University Press, 1995)
Here is a goldmine of information about women's writing, women's history, and women's concerns--over eight hundred entries, ranging from brief identifications to extensive essays. There are nearly four hundred biographical entries, touching on not only important poets, novelists, and playwrights (including such modern figures as Wendy Wasserstein, Anne Tyler, Alice Walker, and Tama Janowitz). Perhaps most important, there is extensive coverage of the many personal, cultural, and historical issues that have been explored by and have influenced the lives and productivity of women writers, including AIDS, race and racism, violence and sexual harassment, the Civil War, the civil rights movement, and much more. There is also coverage of the publishing world (including bookstores and women's presses), the art and practice of writing, and contemporary literary criticism (including lesbian literary theory, black feminism, and deconstruction)